Muscle wasting in the presence of disease, why is it so variable? - Kemp,P; Griffiths,M; Polkey,M (Biological Reviews, 2019)
Skeletal muscle wasting is a common clinical feature of many chronic diseases and also occurs in response to single acute events. The accompanying loss of strength can lead to significant disability, increased care needs and have profound negative effects on quality of life. As muscle is the most abundant source of amino acids in the body, it appears to function as a buffer for fuel and substrates that can be used to repair damage elsewhere and to feed the immune system. In essence, the fundamentals of muscle wasting are simple: less muscle is made than is broken down. However, although welldescribed mechanisms modulate muscle protein turnover, significant individual differences in the amount of muscle lost in the presence of a given severity of disease complicate the understanding of underlying mechanisms and suggest that individuals have different sensitivities to signals for muscle loss. Furthermore, the rate at which muscle protein is turned over under normal conditions means that clinically significant muscle loss can occur with changes in the rate of protein synthesis and/or breakdown that are too small to be measurable. Consequently, the changes in expression of factors regulating muscle turnover required to cause a decline in muscle mass are small and, except in cases of rapid wasting, there is no consistent pattern of change in the expression of factors that regulate muscle mass. MicroRNAs are fine tuners of cell phenotype and are therefore ideally suited to cause the subtle changes in proteome required to tilt the balance between synthesis and degradation in a way that causes clinically significant wasting. Herein we present a model in which muscle loss as a consequence of disease in nonmuscle tissue is modulated by a set of microRNAs, the muscle expression of which is associated with severity of disease in the nonmuscle tissue. These microRNAs alter fundamental biological processes including the synthesis of ribosomes and mitochondria leading to reduce